2008
DOI: 10.1182/blood-2008-04-150862
|View full text |Cite
|
Sign up to set email alerts
|

The neovasculature homing motif NGR: more than meets the eye

Abstract: IntroductionPhage display libraries are often used for discovering peptide sequences that interact with proteins differentially expressed in normal and pathologic tissues. 1,2 Indeed, in vivo panning of peptide-phage libraries in tumor-bearing animal models has proven useful for selecting peptides able to interact with proteins expressed within tumor-associated blood vessels and therefore to home to neoplastic tissues. 3 Among the ligands identified so far, cyclic and linear peptides containing the Asn-Gly-Arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
169
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 176 publications
(177 citation statements)
references
References 78 publications
1
169
0
2
Order By: Relevance
“…CD13 is a membrane protease expressed by endothelial cells of angiogenic vessels and other cells within the tumor stroma (22,24,47). This raises the question as to whether CNGRC plays a role in the synergism with 1-MT.…”
Section: Discussionmentioning
confidence: 99%
“…CD13 is a membrane protease expressed by endothelial cells of angiogenic vessels and other cells within the tumor stroma (22,24,47). This raises the question as to whether CNGRC plays a role in the synergism with 1-MT.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from our laboratory have demonstrated reduction of tumor growth by targeting an isoform of APN expressed in the tumor vasculature with NGR coupled to doxorubicin in murine models (18)(19)(20). These preclinical studies have been followed with phase II/III clinical trials based on NGR genetically fused to tumor necrosis factor α for the treatment of hepatocarcinomas, pleural mesotheliomas, and colorectal cancer (59)(60)(61)(62)(63)(64). The APN-null mouse-based model that we have established here will be useful for further investigation of the role of distinct APN isoforms expressed by individual populations of cells in cancer and of their potential relevance for additional medical applications.…”
Section: Discussionmentioning
confidence: 99%
“…The structural determinants of this selectivity are still unknown. It has been postulated that the use of alternative glycosylation sites or changes in the composition of oligosaccharides may mask antibody or peptide-binding sites (35). Peptide-binding selectivity might also be related to differential formation of quaternary complexes with other proteins in different tissues.…”
Section: Discussionmentioning
confidence: 99%